Empresariado e política externa brasileira: a Confederação Nacional da Indústria e o processo de acessão do Brasil à OCDE - Morais, Guilherme de Paiva (2023)
The entry of Brazil into the OECD has turned, since the official request for entry announced by the government of Michel Temer in 2017, a priority on the international agenda of the National Confederation of Industry (CNI), which will act as one of two main supports for negotiations for or attainment of such objective. The CNI moved to include the entry of the country in the OECD in its priority guideline, undertaking efforts both internally with other business and political actors, as well as externally with their peers, to guarantee the necessary support for the advancement of the domestic and international agenda. That said, it is proposed, through the qualitative analysis of bibliographies, official documents, pronouncements, interviews and reports, to explore and understand, in its dynamics, the conformation of interests of the National Confederation of Industry (CNI) in relation to the Brazilian foreign policy to from 2014, based on the industry's international agenda and its prioritization of negotiations for Brazil's entry as a full member of the OECD, which expresses the evolution of CNI's positions and reflects its redefinitions in the sense of the liberal agenda. Therefore, we argue that, since 2016, the main objective of the National Confederation of Industry has been to restructure the country and its institutions through international governance instruments and the liberal demands promoted by developed countries, adhering to identified standards, systems and behaviors as being of interest to the national industrial business community. Therefore, joining the OECD would be the institution's main strategy for domestic reforms through a lock-in between the organization's standards and Brazilian legislation